Feasibility of hyperspectral imaging as rapid detection tool for potassium sorbate in milk. Issue 4 (21st April 2021) - Wang, Yan; Huang, Yu; Shen, Weizheng; Kong, Fanze; Gao, Meng; Sun, Hongmin
Abstract: Detection of additives in milk is important, especially preservatives. Potassium sorbate was taken as an example to study the feasibility of hyperspectral imaging as a rapid detection tool for preservatives in milk. Samples with different concentrations of potassium sorbate were divided into four groups. Pretreatment and variable selection methods were studied based on the support vector machine model. The model with standard normalized variable pretreatment and competitive adaptive reweighted sampling variable selection had the best performance. Testing set accuracy for different groups from low concentration to high concentration were 92.16%, 95.7%, 99.46%, and 98.33%. Hyperspectral imaging can be a rapid detection tool for potassium sorbate in milk.